2021
DOI: 10.1186/s13041-020-00713-2
|View full text |Cite
|
Sign up to set email alerts
|

Global knockdown of glutamate decarboxylase 67 elicits emotional abnormality in mice

Abstract: Reduced expression of glutamate decarboxylase 67 (GAD67), encoded by the Gad1 gene, is a consistent finding in postmortem brains of patients with several psychiatric disorders, including schizophrenia, bipolar disorder and major depressive disorder. The dysfunction of GAD67 in the brain is implicated in the pathophysiology of these psychiatric disorders; however, the neurobiological consequences of GAD67 dysfunction in mature brains are not fully understood because the homozygous Gad1 knockout is lethal in new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Similarly, animal models support the notion of GABA playing a yet underrated role in the pathophysiology of NDDs. Genetic mouse models with impaired function GABAergic signalling components mirror core ADHD symptoms such as hyperactivity, impaired sustained attention and increased impulsivity [42][43][44][45]. Interestingly, hyperactivity in the Gat1 knockout mice was rescued by stimulant application [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, animal models support the notion of GABA playing a yet underrated role in the pathophysiology of NDDs. Genetic mouse models with impaired function GABAergic signalling components mirror core ADHD symptoms such as hyperactivity, impaired sustained attention and increased impulsivity [42][43][44][45]. Interestingly, hyperactivity in the Gat1 knockout mice was rescued by stimulant application [45].…”
Section: Discussionmentioning
confidence: 99%
“…control and show that foxp2 loss-of-function results in increased locomotor activity. Interestingly, impaired Gad1 function is implicated in altered motor function [43,66]. Hence, we hypothesised that Gad1-activity is important for the regulation of locomotor behaviour in zebrafish larvae.…”
Section: Generation Of a Foxp2 Loss-of-function Mutation By Crispr/ Cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in mice have demonstrated that reducing the expression of GAD67, up to its definitive blocking, causes emotional abnormalities and alters conditioned fear behavior. Thus, the fear of certain objects or certain contexts, which in the past represented a danger, disappears [ 44 ]. GABA synthesis, produced by GAD67, has an important role in the contextualization and differentiation of fear memory.…”
Section: Geneticsmentioning
confidence: 99%
“…GABA plays an important role in improving the physiological function of the body and is often used as a drug and food addition. In the pharmaceutical industry, GABA has an anticonvulsant function [ 1 ] and is used to treat epilepsy [ 2 ], anxiety [ 3 ], and in adjuvant treatment of Parkinson's disease [ 4 ]. As a food addition, GABA is often added to beverages, alcohol, and milk to prevent neurological diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%